2011
DOI: 10.1149/1.3534202
|View full text |Cite
|
Sign up to set email alerts
|

Interface Characterization and Electrical Transport Mechanisms in a-Si:H/c-Si Heterojunction Solar Cells

Abstract: The fabrication of amorphous silicon/crystalline silicon ͑a-Si:H/c-Si͒ heterojunction solar cell and an understanding of the fundamental conduction mechanism in the device are presented. In the first part, the effect of intrinsic amorphous silicon ͓a-Si:H͑i͔͒ layer thickness on the performance of a-Si:H/c-Si solar cells has been studied. The thickness of a-Si:H͑i͒ layer formed on n-type c-Si substrate was controlled accurately with spectroscopy ellipsometry ͑SE͒. Based on SE results, we discuss the influence o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 12 publications
2
12
0
Order By: Relevance
“…Finally, the MLBC solar cell employing a VMV (12 nm Ca) emitter exhibited the lowest value of E a , which may be explained by the fact that the increased recombination in the VMV (12 nm Ca) emitter bulk is due to the existence of a large Schottky barrier and reverse bias. 30 Consequently, the use of a VMV (12 nm Ag) as an emitter in an MLBC solar cell can provides the largest value of E a (E a ¼ 0.75 eV) of all the emitters considered, which is also in good agreement with the increased V OC shown in Fig. 3(d).…”
Section: Resultssupporting
confidence: 77%
See 1 more Smart Citation
“…Finally, the MLBC solar cell employing a VMV (12 nm Ca) emitter exhibited the lowest value of E a , which may be explained by the fact that the increased recombination in the VMV (12 nm Ca) emitter bulk is due to the existence of a large Schottky barrier and reverse bias. 30 Consequently, the use of a VMV (12 nm Ag) as an emitter in an MLBC solar cell can provides the largest value of E a (E a ¼ 0.75 eV) of all the emitters considered, which is also in good agreement with the increased V OC shown in Fig. 3(d).…”
Section: Resultssupporting
confidence: 77%
“…5(c), the diffusion-recombination model is dominant at the interface of VMV (Ag)/n-Si and VMV (Au)/n-Si contacts due to the increase in the exponential factor A with increasing 1/kT. 29,30 Meanwhile, the multi-tunneling capture emission (MTCE) model determined the charge carrier transport property between V 2 O x /n-Si and VMV (Ca)/n-Si contacts at a high forward-bias voltage because the A values remain fairly stable with increasing 1/kT. 31 The MTCE process is more related to the bulk recombination in the emitter than to interface defect states, and, thus, the use of VMV (Ca) as an emitter produces a larger recombination rate and lower V OC , as shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…These E a( J 0) values are less than kT at room temperature and are also less than the energy band gap of a‐Si:H(n) and a‐Si:H(p). Thus, the dominant carrier transports in the n/p junction cannot be the direct tunneling through the barrier . We propose the MTCE model for the present system.…”
Section: Resultsmentioning
confidence: 96%
“…A band bending will occur at the heterojunction and will certainly influence the barrier height at the interface. However, Dao et al [ 19 ] suggested that for interfaces with a high defect density, defect states within the bandgap play a significant role with respect to the barrier height. Therefore, our measured barrier height represents an “effective” barrier height considering band bending, band offset, bandgap widening, and defect state density.…”
Section: Resultsmentioning
confidence: 99%